Prevalence and diversity of Wolbachia bacteria infecting insect pests of stored products. (May 2015) - Li, Y.-Y.; Fields, P.G.; Pang, B.-P.; Coghlin, P.C.; Floate, K.D.
Abstract: Wolbachia are common bacterial symbionts of insects. Because infections of these bacteria can alter the reproduction and biology of the host, there is interest in the potential use of Wolbachia to control populations of pest species. To advance this research, we screened 38 species (88 populations from 16 countries) of stored-product insect pests for Wolbachia infections. Infections were detected in nine species of Coleoptera (Anobiidae – Lasioderma serricorne (Fabricius), Stegobium paniceum (Linnaeus); Curculionidae – Sitophilus oryzae (Motschulsky), Sitophilus zeamais Motschulsky; Dermestidae – Attagenus unicolor (Brahm), Dermestes lardarius Linnaeus; Silvanidae – Oryzaephilus mercator (Fauvel), Oryzaephilus surinamensis (Linnaeus); Tenebrionidae – Tribolium confusum Jaquelin Du Val), one species of Hymenoptera (Trichogrammatidae – Trichogramma deion Pinto & Oatman), and one species of Lepidoptera (Pyralidae – Ephestia kuehniella Zeller). Phylogenetic analyses based on wsp gene sequences identified all Wolbachia isolates as members of Supergroups A or B. Additional sequences for the genes gatB, coxA, hcpA, fbpA and ftsZ were obtained for use in multilocus sequence typing (MLST) to identify the sequence types to which the isolates belonged. Our results identify five new Wolbachia -insect associations and support previous findings that infections of Wolbachia in stored-product insect pests are members of Supergroups A or B. Highlights: Wolbachia are symbiotic bacteria with possible application in pest control. Stored-product insects (n = 38 species) were screened for Wolbachia infection. Infections were detected in 11 species. Results identify five new Wolbachia -insect associations. Phylogenetic analyses identify all isolates as members of Supergroups A or B.